2012
DOI: 10.1115/1.4007097
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Model Predicts Tissue-Level Failure From Collagen Fiber-Level Damage

Abstract: Excessive tissue-level forces communicated to the microstructure and extracellular matrix of soft tissues can lead to damage and failure through poorly understood physical processes that are multiscale in nature. In this work, we propose a multiscale mechanical model for the failure of collagenous soft tissues that incorporates spatial heterogeneity in the microstructure and links the failure of discrete collagen fibers to the material response of the tissue. The model, which is based on experimental failure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 43 publications
2
40
0
Order By: Relevance
“…It should be noted that such a feedback loop is not necessary to obtain the mechanical environment of cartilage and chondrocytes for a given tissue state. It will be necessary when constitutive properties change as a result of tissue growth and damage [31]. Nonetheless, the tools presented in this study can be adapted for such purposes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that such a feedback loop is not necessary to obtain the mechanical environment of cartilage and chondrocytes for a given tissue state. It will be necessary when constitutive properties change as a result of tissue growth and damage [31]. Nonetheless, the tools presented in this study can be adapted for such purposes.…”
Section: Discussionmentioning
confidence: 99%
“…incorporating the cytoskeleton (actin and tubulin) [30], to understand the mechanical load transmission to intracellular components, in particular to the nucleus. Similar submodelling can be performed for the extracellular matrix, for example, to evaluate microstructural-level loading of collagen fibres, which may provide the relationship between macroscopic tissue damage accumulation and microscale fibre failure [31]. At all spatial scales, it is also possible to increase the fidelity of mechanical representation; in terms of physics (nonlinear elasticity, multiphasic response) [32], with additional anatomical components, and by using more advanced constitutive relationships [24,33].…”
Section: High-throughput Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study also indicated that intrinsic elastic properties dictate distensibility of the aorta [34]. In addition, a collagen-based fiber network would not be able to achieve a stretch of 2.0 since collagen fibers have a k crit closer to 1.4 [17], while elastin can reach stretches up to 3 [35]. Histological evidence supports a large elastin contribution as studies have shown more elastin than collagen exists in the ascending aorta (by dry weight 35% elastin, 22% collagen [19]).…”
Section: Discussionmentioning
confidence: 99%
“…2, Refs. [14,15,17]) was made up of elements at three scales: the finite element (FE) domain at the millimeter (mm) scale, representative volume elements (RVE) at the micrometer (lm) scale, and the fibers with radii at the Each element consists of eight Gauss points that dictate its stress-strain response. Each Gauss point consists of representative volume elements (RVE) that consist of a nanoscale fiber network in parallel with a nearly incompressible neoHookean matrix.…”
Section: Methods: Modelmentioning
confidence: 99%